A new type of hydraulic cylinder system controlled by the new-type hydraulic transformer. (August 2014) - Shen, Wei; Jiang, Jihai; Su, Xiaoyu; Karimi, Hamid Reza
In order to enhance the efficiency of the hydraulic system, one new-type hydraulic transformer is presented in this paper. First, the basic structure and the principle of the new-type hydraulic transformer are explained. Then, the mathematical models including both the inner and outer loops are analyzed. Moreover, two kinds of control methods are discussed corresponding to the two loops, respectively. Furthermore, the proposed strategies are translated into the simulation languages, and the simulation is made in Simulink. Finally, the prototypes of new-type hydraulic transformer and the test rig are constructed to test the performance. Both the simulated and experimental results show that the new-type hydraulic transformer can be used in the practical condition, and the proposed control algorithm is suitable.